Additive manufacturing method suitable for high-crack-sensitivity alloy
By adopting dual laser treatment for high-crack-sensitive alloys in additive manufacturing, pre-sintering and Gaussian lasers for scanning and sintering, the problem of high-crack-sensitive alloys prone to cracks in additive manufacturing is solved, and the effect of reducing crack risks and improving material quality is achieved.
Patent Information
- Application Number
- CN202510018771.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-06
AI Technical Summary
High crack-sensitive alloys are prone to cracks during additive manufacturing, resulting in a decline in the comprehensive mechanical properties of the product and failing to meet the application requirements.
Using laser powder bed melting technology, each layer of metal powder is subjected to double laser treatment. First, a homogenized laser is used to presintered to obtain a presintered body, and then a Gaussian laser is used to scan and sinter. The spot diameter of the homogenized laser is 100-500 μm and the power is 800-2000 W; the spot diameter of the Gaussian laser is 40-100 μm and the power is 80-500 W.
It effectively reduces the crack risk of high-crack-sensitive alloys throughout the additive manufacturing process, without high-temperature preheating, reduces manufacturing costs, and improves the fineness and surface quality of the material.
Smart Images

Figure CN119634750A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing, and in particular relates to a method for additive manufacturing using a high crack sensitivity alloy. Background Art
[0002] Additive manufacturing is a technology that manufactures three-dimensional products by adding materials layer by layer, melting them through a heat source, and cooling them to solidify. Unlike traditional subtractive manufacturing methods, additive manufacturing can achieve highly complex structural designs, reduce material waste, and shorten product development cycles. In recent years, additive manufacturing technology has received widespread attention in aerospace, medical, automotive, and electronics fields.
[0003] At present, additive manufacturing technologies include laser powder bed fusion (L-PBF), laser directed energy deposition (L-DED), electron beam melting (EBM), stereolithography (SLA), etc. Each technology has its own characteristics in terms of material type, manufacturing speed and precision, and application field. Laser powder bed fusion (L-PBF) is to spread the metal powder evenly on the substrate, and then scan a specific area with a laser. The laser beam is irradiated onto the powder bed, so that the powder in the selected area is quickly melted into liquid. As the laser moves, the liquid metal gradually cools and solidifies to form the first layer of structure; the automatic powder spreading device covers a new layer of metal powder on the surface of the formed structure and scans the laser again; repeat this process until the entire part is completed. The characteristic of L-PBF is that it can achieve micron-level printing accuracy, which is suitable for manufacturing complex and delicate parts and provides greater design freedom.
[0004] However, L-PBF cannot be used for alloys with high crack sensitivity. During the forming process, defects such as pores and cracks are prone to occur in alloys with high crack sensitivity, which will reduce the comprehensive mechanical properties of the product and thus fail to meet the application requirements. This is because alloys with high crack sensitivity are prone to thermal stress and residual stress during melting and cooling, which lead to the generation and expansion of cracks, especially in the case of rapid cooling, with large temperature gradients and local stress concentration; some alloys with high crack sensitivity may also undergo phase change or element segregation during the melting process, resulting in uneven material properties, and the volume change caused by phase change and the interaction between different phases may further aggravate the formation of cracks.
[0005] In order to solve the problem that highly crack-sensitive alloys are prone to cracking during additive manufacturing, the method of preheating the substrate is generally adopted. By increasing the temperature of the substrate, especially in the early stage of printing, the temperature gradient of the molten pool can be reduced, and the concentration of thermal stress can be reduced, thereby reducing the risk of alloy cracks. However, substrate preheating requires a relatively high temperature, sometimes reaching 1000°C or even higher. The high temperature environment imposes a greater burden on the equipment, accelerates equipment wear and aging, and increases manufacturing costs; and substrate preheating only has a good effect in the early stage of printing, and has limited improvement effects in the middle and late stages. Summary of the invention
[0006] The purpose of the present invention is to provide a method for additive manufacturing of highly crack-sensitive alloys. The method provided by the present invention can reduce the crack risk of highly crack-sensitive alloys in the entire additive manufacturing process, and does not require high-temperature preheating, thereby reducing manufacturing costs.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides an additive manufacturing method suitable for high crack sensitivity alloys. The additive manufacturing is performed by laser powder bed melting technology, and each layer of metal powder is processed by dual lasers, including: firstly, the metal powder is pre-sintered by a homogenizing laser to obtain a pre-sintered body, and then the pre-sintered body is scanned and sintered by a Gaussian laser; the spot diameter of the homogenizing laser is 100 to 500 μm, and the power is 800 to 2000 W; the spot diameter of the Gaussian laser is 40 to 100 μm, and the power is 80 to 500 W.
[0009] Preferably, the high crack sensitivity alloy includes aluminum alloy, nickel-based high temperature alloy, stainless steel, TiAl alloy or NiAl alloy.
[0010] Preferably, when the solidification range of the high crack sensitivity alloy is higher than 350K, the dual laser processing of each layer of metal powder includes: first using a homogenizing laser to pre-sinter the metal powder as a whole to obtain a pre-sintered body, dividing the pre-sintered body into a solid area and a border area surrounding the solid area according to the target area, the width of the border area is 0.1 to 0.5 mm, and then using a Gaussian laser to scan and sinter the solid area.
[0011] Preferably, when the solidification range of the high crack sensitivity alloy is between 265K and 350K, the dual laser processing of each layer of metal powder includes: dividing the metal powder into a solid area and a border area surrounding the solid area according to the target area, the width of the border area is 0.1 to 0.5 mm, first using a homogenizing laser to pre-sinter the solid area to obtain a pre-sintered body, and then using a Gaussian laser to scan and sinter the border area.
[0012] Preferably, the scanning speed of the homogenization laser is 100-7000 mm / s.
[0013] Preferably, the scanning speed of the Gaussian laser is 100-3000 mm / s.
[0014] Preferably, during the additive manufacturing, the printed substrate and the metal powder are made of the same material.
[0015] Preferably, the metal powder is dried before use, the drying temperature is 70-90° C., and the drying time is 4-6 hours.
[0016] Preferably, the additive manufacturing is performed in an inert atmosphere.
[0017] Preferably, the thickness of each layer of metal powder is independently 30 to 200 μm.
[0018] The present invention provides an additive manufacturing method suitable for high crack sensitivity alloys. The additive manufacturing is performed by laser powder bed melting technology, and each layer of metal powder is processed by dual lasers, including: firstly, the metal powder is pre-sintered by a homogenizing laser to obtain a pre-sintered body, and then the pre-sintered body is scanned and sintered by a Gaussian laser; the spot diameter of the homogenizing laser is 100 to 500 μm, and the power is 800 to 2000 W; the spot diameter of the Gaussian laser is 40 to 100 μm, and the power is 80 to 500 W. The present invention utilizes the characteristics of large homogenized laser spot diameter, high laser power, and uniform energy distribution to pre-sinter metal powder, which can realize the effect of preheating the substrate. In the middle and late stages of additive manufacturing, it can realize the preheating of the formed material; then Gaussian laser is used for processing, which reduces the temperature difference between the molten pool and the substrate (or the formed material), reduces the temperature gradient, reduces the thermal stress during the cooling process, reduces stress concentration, and thus reduces the formation and expansion of cracks; utilizing the characteristics of small Gaussian laser spot diameter and concentrated energy, the pre-sintered alloy is subjected to secondary scanning sintering, which can make the material finer, eliminate possible problems such as uneven material distribution and surface defects, further reduce the risk of cracks, and is suitable for additive manufacturing of high crack-sensitive alloys. The results of the embodiment show that the method provided by the present invention can effectively suppress cracks in high crack-sensitive alloys in additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic flow chart of an additive manufacturing method for highly crack-sensitive alloys provided by the present invention;
[0020] Figure 2 A schematic diagram of the structure of a dual laser system used in additive manufacturing of the present invention;
[0021] Figure 3 A schematic diagram of the partition processing of a high crack sensitivity alloy according to the present invention;
[0022] Figure 4 A schematic diagram of the spot shape and energy distribution of the homogenized laser used in an embodiment of the present invention;
[0023] Figure 5 A schematic diagram of the spot shape and energy distribution of the Gaussian laser used in an embodiment of the present invention;
[0024] Figure 6 This is a metallographic optical microscope image of the TiAl alloy formed by processing in Example 1 of the present invention;
[0025] Figure 7 This is a metallographic optical microscope image of the IN939 alloy formed by processing in Example 2 of the present invention;
[0026] Figure 8 This is a metallographic optical microscope image of the TiAl alloy formed by the comparative example 1 of the present invention;
[0027] Fig. 9 This is a metallographic optical microscope image of the IN939 alloy formed by comparative example 2 of the present invention. DETAILED DESCRIPTION
[0028] The present invention provides an additive manufacturing method suitable for high crack sensitivity alloys. The additive manufacturing is performed by laser powder bed melting technology, and each layer of metal powder is processed by dual lasers, including: firstly, the metal powder is pre-sintered by a homogenizing laser to obtain a pre-sintered body, and then the pre-sintered body is scanned and sintered by a Gaussian laser; the spot diameter of the homogenizing laser is 100 to 500 μm, and the power is 800 to 2000 W; the spot diameter of the Gaussian laser is 40 to 100 μm, and the power is 80 to 500 W.
[0029] In the present invention, the high crack sensitivity alloy preferably includes aluminum alloy, nickel-based high temperature alloy, stainless steel, TiAl alloy or NiAl alloy.
[0030] The present invention has no special requirements on the type of the high crack sensitivity alloy, and all high crack sensitivity alloys can be additively manufactured using the method of the present invention.
[0031] The present invention adopts laser powder bed melting technology to perform additive manufacturing.
[0032] In the present invention, the printing substrate is preferably made of the same material as the metal powder during additive manufacturing. The printing substrate and the metal powder are made of the same material, so that the printing substrate and the forming material have similar heat transfer properties, which is conducive to the stable forming of the material on the printing substrate.
[0033] In the present invention, the additive manufacturing is preferably carried out in an inert atmosphere. The present invention has no particular requirements for the specific type of the inert atmosphere, and the inert atmosphere commonly used in the art can be used; in the embodiment of the present invention, argon or helium is used to reduce the oxygen content to below 800 ppm. Additive manufacturing in an inert atmosphere can prevent metal from being oxidized, which is conducive to improving material quality.
[0034] In the present invention, the printed substrate is preferably subjected to surface treatment before the additive manufacturing, and the surface treatment is preferably sandblasting. By performing surface treatment on the printed substrate, dirt, oxide layer and other impurities on the surface of the printed substrate are removed, which is beneficial to the combination of the forming material and the printed substrate.
[0035] When performing additive manufacturing, the present invention uses dual laser processing for each layer of metal powder.
[0036] In the present invention, the metal powder is preferably dried before use, and the drying temperature is preferably 70-90°C, more preferably 75-85°C; the drying time is preferably 4-6 hours, more preferably 4.5-5.5 hours. Drying the metal powder can reduce the moisture content of the metal powder, prevent agglomeration, improve the fluidity of the powder, and facilitate uniform powder spreading.
[0037] In the present invention, the thickness of each layer of metal powder is independently preferably 30 to 200 μm, more preferably 30 to 100 μm; as an embodiment of the present invention, the thickness of the metal powder can be 35 μm, 40 μm, 45 μm, 55 μm, 65 μm, 75 μm, 85 μm, 110 μm, 150 μm or 180 μm. The thickness of each layer of metal powder within the above range is conducive to improving the uniformity of the material.
[0038] As an embodiment of the present invention, when the solidification interval of the high crack sensitivity alloy is higher than 350K, the dual laser processing of each layer of metal powder preferably includes: firstly using a homogenizing laser to pre-sinter the metal powder as a whole to obtain a pre-sintered body, dividing the pre-sintered body into a solid area and a frame area surrounding the solid area according to the target area, the width of the frame area is 0.1 to 0.5 mm, and then using a Gaussian laser to scan and sinter the solid area. When the solidification interval of the alloy is higher than 350K, the crack sensitivity of the alloy is very high. The present invention uses a homogenizing laser for pre-sintering, uses a Gaussian laser for secondary sintering of the solid area, and does not use a Gaussian laser to scan and sinter the frame area, which can further reduce the risk of cracks.
[0039] As another embodiment of the present invention, when the solidification interval of the high crack sensitivity alloy is between 265K and 350K, the dual laser processing of each layer of metal powder preferably includes: dividing the metal powder into a solid area and a frame area surrounding the outer periphery of the solid area according to the target area, the width of the frame area is 0.1 to 0.5 mm, firstly using a homogenization laser to pre-sinter the solid area to obtain a pre-sintered body, and then using a Gaussian laser to scan and sinter the frame area. When the solidification interval of the alloy is between 265K and 350K, the crack sensitivity of the alloy is relatively high. The present invention uses a homogenization laser to pre-sinter the solid area, which can increase the temperature of the substrate (or formed material), and uses a Gaussian laser to sinter the frame area, which can reduce the temperature gradient, which is conducive to reducing the risk of cracks, and can also improve the surface quality of the frame area.
[0040] In the present invention, the spot diameter of the homogenization laser is 100-500 μm, preferably 200-400 μm, and more preferably 250-350 μm. As an embodiment of the present invention, the spot diameter of the homogenization laser can be 220 μm, 280 μm, 330 μm, 360 μm, 390 μm, 420 μm or 450 μm. The spot diameter of the homogenization laser has a larger molten pool area in the above range, can provide uniform energy distribution, can reduce stress concentration, and reduce the occurrence of cracks.
[0041] In the present invention, the power of the homogenization laser is 800-2000W, preferably 1200-1600W, and more preferably 1400-1500W. As an embodiment of the present invention, the power of the homogenization laser can be 850W, 950W, 1100W, 1250W, 1300W, 1450W, 1700W, 1800W or 1900W. The power of the homogenization laser affects the temperature of scanning sintering. When the power of the homogenization laser is within the above range, the metal powder can be melted, and the printed substrate or the formed material can be effectively preheated, the temperature gradient can be reduced, and the occurrence of cracks can be reduced, while also avoiding burn-through due to excessive power.
[0042] In the present invention, the spot diameter of the Gaussian laser is 40 to 100 μm, preferably 50 to 80 μm, and more preferably 60 to 70 μm. As an embodiment of the present invention, the spot diameter of the Gaussian laser may be 45 μm, 55 μm, 65 μm, 75 μm, 85 μm, 90 μm or 95 μm. In the present invention, the power of the Gaussian laser is 80 to 500 W, preferably 200 to 400 W, and more preferably 250 to 350 W. As an embodiment of the present invention, the power of the Gaussian laser may be 100 W, 150 W, 220 W, 280 W, 300 W, 330 W, 370 W, 420 W or 450 W. The spot diameter and power of the Gaussian laser in the above range can scan and sinter the material more finely, eliminate possible material unevenness, surface defects, etc., and reduce the occurrence of cracks.
[0043] In the present invention, the scanning speed of the homogenizing laser is preferably 100-7000 mm / s, more preferably 500-2000 mm / s; as an embodiment of the present invention, the scanning speed of the homogenizing laser can be 600 mm / s, 900 mm / s, 1200 mm / s, 1500 mm / s, 3000 mm / s, 4000 mm / s or 6000 mm / s. When the scanning speed of the homogenizing laser is within the above range, both product quality and processing speed can be taken into account.
[0044] In the present invention, the scanning speed of the Gaussian laser is preferably 100-3000 mm / s, more preferably 500-1000 mm / s; as an embodiment of the present invention, the scanning speed of the Gaussian laser can be 400 mm / s, 600 mm / s, 700 mm / s, 1100 mm / s, 1300 mm / s, 1800 mm / s, 2000 mm / s or 2500 mm / s. The scanning speed of the Gaussian laser is within the above range, which can take into account both product quality and processing speed.
[0045] The present invention has no special requirements for other operations of the additive manufacturing, and it can be done according to the conventional additive manufacturing process in the field. As an embodiment of the present invention, the additive manufacturing process can be: sandblasting the printing substrate; drying the metal powder; mounting the sandblasted printing substrate on the stage and fixing it, and lowering the printing substrate to below the printing level using a lifting platform; replacing the inert gas using an exhaust system; performing manual zeroing to keep the printing substrate at the same height as the printing level; rotating the powder shaft to lower the metal powder, and using a scraper to spread the powder; slicing the completed model and inputting the corresponding process parameters into the control system, and using dual lasers for sintering; starting automatic printing, and repeating the powder spreading-sintering process for each layer until the final layer, to obtain an additive manufacturing part.
[0046] The schematic diagram of the process of additive manufacturing using laser powder bed melting technology in the present invention is as follows Figure 1 As shown: Slicing is performed according to the 3D model information of the metal part; dual laser system printing is selected according to the slicing information; for high crack sensitivity alloys with a solidification range greater than 350K, a homogenizing laser is first used for pre-sintering to preheat the powder bed, and then a Gaussian laser is used for reprocessing; for high crack sensitivity alloys with a solidification range between 260K and 350K, a homogenizing laser is first used to sinter the solid area, and then a Gaussian laser is used to sinter the border area; the dual laser printing process of all layers is completed to obtain parts of high crack sensitivity alloys.
[0047] The present invention utilizes the characteristics of large homogenized laser spot diameter, high laser power, and uniform energy distribution to pre-sinter metal powder, thereby preheating the substrate. In the middle and late stages of additive manufacturing, preheating of the formed material can be achieved. When Gaussian laser is used for processing, the temperature difference between the molten pool and the substrate (or the formed material) is reduced, the temperature gradient is reduced, the thermal stress in the cooling process is reduced, the stress concentration is reduced, and thus the formation and expansion of cracks are reduced. Utilizing the characteristics of small Gaussian laser spot diameter and concentrated energy, the pre-sintered alloy is subjected to secondary scanning sintering, which can make the material finer, eliminate possible problems such as uneven material distribution and surface defects, and further reduce the risk of cracks.
[0048] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1
[0050] A method for additive manufacturing of a high crack sensitivity alloy, wherein the high crack sensitivity alloy is a Ti-48Al-2Cr-2Nb alloy, referred to as a TiAl alloy, and has a solidification range of 417K. The schematic diagram of the additive manufacturing equipment is as follows Figure 2 As shown in the figure, 1 and 2 are galvanometers, 3 is a formed material, 4 is metal powder, 5 is a printing substrate, 6 is a stage, 7 is a lifting platform, 8 is a Gaussian laser, 9 is a homogenizing laser, 10 is a computer, 11 is a Gaussian laser, 12 is a homogenizing laser, and 13 is a printing direction.
[0051] The schematic diagram of the partition processing of the TiAl alloy in this embodiment is as follows Figure 3 As shown, 14 is a border area with a width of 0.1 mm, and 15 is a solid area.
[0052] The spot shape and energy distribution diagram of the uniform laser in this embodiment are shown in FIG. Figure 4 As shown, the spot diameter is 400 μm.
[0053] The schematic diagram of the spot shape and energy distribution of the Gaussian laser in this embodiment is as follows Figure 5 As shown, the spot diameter is 80 μm.
[0054] The specific steps of additive manufacturing are:
[0055] Step 1: Place the printed substrate 5 in a sandblasting machine and perform sandblasting on each surface of the substrate. After the sandblasting is completed, use the compressed air gun in the sandblasting machine to remove the gravel attached to the substrate, use high-grade wipe paper dipped in alcohol to wipe the surface in one direction, and use a dryer to dry for 5 minutes for standby use; the printed substrate 5 is a TiAl alloy substrate with a size of 248mm*248mm*30mm;
[0056] Step 2: Put the metal powder 4 of TiAl alloy into an oven for drying; the drying temperature is 80° C. and the drying time is 5 hours;
[0057] Step 3: Place the sandblasted printed substrate 5 on the stage 6 and fix it with screws, and use the mechanical lifting platform 7 to lower the printed substrate 5 to 4 cm below the printing level;
[0058] Step 4: Open the exhaust system and introduce argon gas until the oxygen content is less than 800 ppm;
[0059] Step 5: Perform manual zeroing to keep the printing substrate 5 at the same height as the printing horizontal surface;
[0060] Step 6: Turn the powder shaft 0.3 turns, drop an appropriate amount of powder, and use a scraper to spread the powder. The scraper advances at a speed of 80 mm / s, a forward distance of 500 mm, and a powder thickness of 30 μm.
[0061] Step 7: Slice the established model and input the corresponding process parameters. First, start the homogenization laser 9, and use the homogenization laser 12 to scan in the printing direction 13 for pre-sintering. The laser power is 800W, the scanning speed is 550mm / s, and the scanning spacing is 250μm. Then, start the Gaussian laser 8, and use the Gaussian laser 11 to scan the solid area 15. The laser power is 100W, the scanning speed is 450mm / s, and the scanning spacing is 50μm. Complete the sintering of one layer;
[0062] Step 8: Turn on automatic printing and repeat steps 6 to 7 for each layer until the final layer to obtain an additively manufactured part.
[0063] Example 2
[0064] A method for additive manufacturing of a high crack sensitivity alloy, wherein the high crack sensitivity alloy is IN939 alloy with a solidification range of 343K. The specific steps of additive manufacturing are:
[0065] Step 1: Place the printed substrate 5 in a sandblasting machine and perform sandblasting on each surface of the substrate. After the sandblasting is completed, use the compressed air gun in the sandblasting machine to remove the sand attached to the substrate. Use high-grade wipe paper dipped in alcohol to wipe the surface in one direction, and use a dryer to dry for 5 minutes for standby use. The printed substrate 5 is an IN939 alloy substrate with a size of 248mm*248mm*30mm.
[0066] Step 2: Put the metal powder 4 of IN939 alloy into an oven for drying; the drying temperature is 80° C. and the drying time is 6 hours;
[0067] Step 3: Place the sandblasted printed substrate 5 on the stage 6 and fix it with screws, and use the mechanical lifting platform 7 to lower the printed substrate 5 to 4 cm below the printing level;
[0068] Step 4: Open the exhaust system and introduce argon gas until the oxygen content is less than 800 ppm;
[0069] Step 5: Perform manual zeroing to keep the printing substrate 5 at the same height as the printing horizontal surface;
[0070] Step 6: Turn the powder shaft 0.3 turns, drop an appropriate amount of powder, and use a scraper to spread the powder. The scraper advances at a speed of 80 mm / s, a forward distance of 500 mm, and a powder thickness of 30 μm.
[0071] Step 7: Slice the established model and input the corresponding process parameters. First, turn on the homogenization laser 9, and use the homogenization laser 12 to pre-sinter the solid area 15 according to the printing direction 13. The laser power is 850W, the scanning speed is 1000mm / s, and the scanning spacing is 300μm. Then turn on the Gaussian laser 8 and use the Gaussian laser 11 to scan the border area 14 (width is 0.1mm). The laser power is 270W, the scanning speed is 1800mm / s, and the scanning spacing is 50μm to complete the sintering of one layer.
[0072] Step 8: Turn on automatic printing and repeat steps 6 to 7 for each layer until the final layer to obtain an additively manufactured part.
[0073] Comparative Example 1
[0074] A method for additive manufacturing, the raw materials and preparation method are the same as those in Example 1, except that only one scanning sintering is performed using a Gaussian laser.
[0075] Comparative Example 2
[0076] A method for additive manufacturing, the raw materials and preparation method are the same as those in Example 2, except that only one scanning sintering is performed using a Gaussian laser.
[0077] The alloy parts obtained by Examples 1 and 2 and Comparative Examples 1 and 2 were observed using a metallographic optical microscope to obtain metallographic images. Figures 6 to 9 shown.
[0078] By comparison Figure 6 and Figure 8 It can be seen that the alloy parts processed in Example 1 control macro cracks into micro cracks, and the crack suppression effect is very significant.
[0079] By comparison Figure 7 and Fig. 9 It can be seen that the alloy parts processed in Example 2 effectively eliminate the cracks generated by Gaussian laser scanning.
[0080] It can be seen from the above embodiments and comparative examples that the method provided by the present invention can effectively inhibit the generation and development of cracks in highly crack-sensitive alloys during additive manufacturing.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for additive manufacturing of highly crack-sensitive alloys, using laser powder bed fusion technology for additive manufacturing, characterized in that: Each layer of metal powder is processed by dual lasers, including: first using a homogenizing laser to pre-sinter the metal powder to obtain a pre-sintered body, and then using a Gaussian laser to scan and sinter the pre-sintered body; the spot diameter of the homogenizing laser is 100 to 500 μm, and the power is 800 to 2000 W; the spot diameter of the Gaussian laser is 40 to 100 μm, and the power is 80 to 500 W.
2. The method according to claim 1, characterized in that The high crack sensitivity alloy includes aluminum alloy, nickel-based high temperature alloy, stainless steel, TiAl alloy or NiAl alloy.
3. The method according to claim 1 or 2, characterized in that: When the solidification range of the high crack sensitivity alloy is higher than 350K, the dual laser processing of each layer of metal powder includes: firstly using a homogenizing laser to pre-sinter the metal powder as a whole to obtain a pre-sintered body, dividing the pre-sintered body into a solid area and a frame area surrounding the solid area according to the target area, the width of the frame area is 0.1 to 0.5 mm, and then using a Gaussian laser to scan and sinter the solid area.
4. The method according to claim 1 or 2, characterized in that: When the solidification range of the high crack sensitivity alloy is between 265K and 350K, the dual laser processing of each layer of metal powder includes: dividing the metal powder into a solid area and a border area surrounding the solid area according to the target area, the width of the border area is 0.1 to 0.5 mm, first using a homogenizing laser to pre-sinter the solid area to obtain a pre-sintered body, and then using a Gaussian laser to scan and sinter the border area.
5. The method according to claim 1, characterized in that The scanning speed of the homogenization laser is 100-7000 mm / s.
6. The method according to claim 1, characterized in that The scanning speed of the Gaussian laser is 100-3000 mm / s.
7. The method according to claim 1, characterized in that During the additive manufacturing, the printed substrate and the metal powder are made of the same material.
8. The method according to claim 1, characterized in that The metal powder is dried before use, the drying temperature is 70-90° C., and the drying time is 4-6 hours.
9. The method according to claim 1, characterized in that: The additive manufacturing is performed in an inert atmosphere.
10. The method according to claim 1, characterized in that The thickness of each layer of metal powder is independently 30 to 200 μm.
Citation Information
Patent Citations
In-situ energy controlled selective laser melting device and method
CN111842892A
Additive manufacturing method for eliminating cracks
CN113649593A
Dual-laser composite system and dual-laser scanning method
CN114643369A
Additive manufacturing systems and methods
US20170106477A1
Method and apparatus for forming holes in brittle materials assisted by stress reduction through heating
US20220288723A1
Cited By
Method and equipment for inhibiting crack defect of difficult-to-weld high-temperature alloy in laser additive manufacturing
CN120839089A
A method of additive manufacturing of a high crack sensitive aluminum alloy
CN122606007A